Caso Dermatológico: mastocitoma cutâneo - Oliveira, A. (2012)
Mastocytoma is a condition that occurs in infants, characterized by localized mast cell hyperplasia and release of their mediators. It may be present at birth or may arise during infancy, and represents approximately 15 -20% of all childhood mastocytosis lesions. It usually appears in infants as a single yellow–tan, round to oval nodule or plaque. The diagnosis is based on the clinical appearance of the lesions and elicitation of Darier’s sign, and confi rmed by biopsy which shows mast cell hyperplasia. We report the case of a child with a solitary mastocytoma of the scalp.